Les cinq premières Lettres Festales de Saint Athanase d'Alexandrie. Un test - Devos, Paul (Analecta Bollandiana, 1992)
The 'first five' Festal Letters (329-333) of Athanasius are selected here as samples. The question is, which are the first five. Are they indeed the traditional nos. 1, 2, 3, 4, 5, and not, rather, nos. 1, 24, 14, 4 and 5, as suggested by the 'new chronology'? The test of 'internal cohesion' seems to the present writer favourable to these latter, adding further to the weight of arguments already adduced.